Cellulose-based magnetoelectric composites - Yan Zong (Nature Portfolio, 2017)
Magnetoelectric materials by converting a magnetic input to a voltage output holds promise in contactless electrodes that find applications from energy harvesting to sensing. Zong et al. report a promising laminate composite that combines a piezoelectric biopolymer, cellulose, and a magnetic material.